Effect of the addition of kañiwa (Chenopodium pallidicaule) flour on textural, physical, and sensory properties of pound cakes - youngsoon, kim; Kim, Dasol; Oh, Hyeonbin (Progress in Nutrition, 2022)
This study examined the effect of kañiwa flour as gluten-free material on pound cake quality. The wheat flour to make pound cake (control, designated as CON) was gradually replaced with different amounts of kañiwa flour (25, 50, 75, and 100%, designated as KF25–KF100, respectively). Batter properties were evaluated by specific gravity and baking loss. The quality of the pound cake was evaluated by determining the physical and textural properties. A sensory evaluation was further done. The incorporation of kañiwa flour in wheat flour significantly affected the physical properties of the batter and the cakes. As the amount of kañiwa flour increased, baking loss, height, and volume were reduced. KF100 showed the best textural properties with respect to hardness, fracturability, and chewiness. Regarding the micrograph of crumbs, with increasing content of kañiwa flour, the pore sizes gradually decreased and starch granules on the matrix surface grew larger. The substitution with kañiwa flour resulted in higher amounts of total polyphenols and flavonoids, and a higher value of the reducing power. The sensory evaluation showed that KF25 scored high with respect to texture, sweetness, bitterness, and overall acceptability in comparison to CON. These results suggest that kañiwa can potentially be applied to develop gluten-free foods.